Numerical modelling of shoreline evolution in the Aveiro coast, Portugal – climate change scenarios - Pereira, Carla (2018)
In the Northwest coast of Portugal, the shoreline evolution is leading to several problems, such as loss of territory and infrastructural damages, mainly caused by the sea wave’s action. This study aims to predict the impacts of climate change on the shoreline evolution in this coastal area. Coastal stretches studied were Esmoriz-Furadouro and Vagueira- Mira, due to their vulnerability related with the low lying sandy coast, the deficit of sediments, the presence of urban waterfronts and the narrow width of the sand spit that separates the ocean from the Aveiro lagoon. The paper describes the application of two shoreline evolution models (LTC and GENESIS) to the projection of shoreline evolution between 2010 and 2100. A reference scenario considering the present typical wave climate and the mean sea water level was compared with 3 other future scenarios that may result from climate change effects, combining different wave climates and mean sea levels (0.42 and 0.64 m above present level). Considering the numerical models' results, maps of the shoreline position were represented every 30 years. The results allowed the analysis of the shoreline retreat, the areas of lost territory and the alongshore sediment transport volumes in several cross sections. A strong trend of shoreline retreat was found for all the scenarios, although the retreat rates tend to decrease along time. Comparing the reference scenario with the climate change scenarios, a slight clockwise rotation of the shoreline was predicted, also increasing the average shoreline retreat from 6% to 11%, depending on the considered scenario.